Building beginners’ self-confidence in speaking at private high school in Makassar - Vivit Rosmayanti; Ramli Ramli; Rafiqa Rafiqa (EduLite: Journal of English Education, Literature and Culture, 2023)
Teaching spoken English has been a critical issue in the EFL context. The researchers are focusing on how to improve students' public speaking abilities. Several studies, however, have focused on how teachers build EFL learners' self-confidence before focusing on their speaking skills. Lack of self-confidence makes it difficult for beginners to speak, and it also makes it difficult for teachers to design activities that foster students' self-confidence. In response to this growing demand, this article provides an empirical account of how scripted role-plays are used as an innovative learning design in a private high school setting with a majority of students who are beginners. This research applied the Classroom Action Research study. The scripted role-play intervention was carried out for eight meetings following an action research protocol. Classroom observations and semi-structured interviews with students and the teacher were used to collect data. Interpretative Phenomenological Analysis (IPA) was used to analyze these data. According to the study's findings, the students had finally gained confidence in public speaking. Being confident allowed students to practice more, which improved their speaking skills. The study's findings have three practical implications. First, increasing opportunities for students to practice speaking should be prioritized in EFL classes. Second, providing scripted role-play for beginner students allows them to easily use the language. Finally, before asking students to improve their speaking skills, teachers should focus on developing their students' self-confidence.